Development of an indirect ELISA for the diagnosis of Feline Immunodeficiency Virus - Alves, Fabiana (2013)
ABSTRACT. Alves F., Mazur C., Rajão D. de S., Diniz R.S., Del Puerto H.L., Braz G.F., Vieira F. de O., Leite R.C., Martins A. de S. & dos Reis J.K.P. Development of an indirect ELISA for the diagnosis of Feline Immunodeficiency Virus. [Desenvolvimento de um ELISA indireto para o diagnóstico do Vírus da Imunodeficiência Felina]. Revista Brasileira de Medicina Veterinária, 35(3):241-246, 2013. Departamento de Fisiologia e Biofísica, Instituto de Ciências Biológicas, Universidade Federal de Minas Gerais, Av. Antônio Carlos 6627, Pampulha, Belo Horizonte, MG 31270-901, Brasil. E-mail: alves.bio@gmail.com The objective of this study was to develop an indirect ELISA (r-p24 ELISA) for the diagnosis of Feline Immunodeficiency virus (FIV-B). Serum samples of 150 asymptomatic cats, of both sexes and mixed breeds and ages were used. The SNAP Combo Plus commercial kit was used as the gold standard. The r-p24 ELISA was standardized using 0.25 µg of recombinant p24 protein (r-p24) per well, serum was diluted at 1:320 and the conjugate was diluted at 1:7500. The r-p24 ELISA showed a sensitivity of 97% and specificity of 93% when compared to the gold standard with a concordance of 83%. When compared to the Western blot confirmatory test, the r-p24 ELISA showed a sensitivity of 94% and specificity of 94% with a concordance of 84%. Therefore, the standardized ELISA is an important tool for the FIV related research and for the FIV diagnosis at low cost.